The Challenging Road to Reconciliation in Rwanda: Societal Processes, Interventions and Their Evaluation - Ervin Staub (Journal of Social and Political Psychology, 2014)
This article briefly discusses some efforts that Rwanda has made to recover from the genocide, ranging from trying perpetrators to creating just social arrangements. It also discusses problematic policies and practices that may interfere with reconciliation. It then describes work the author and his associates have engaged in to promote healing and reconciliation in Rwanda. First, they conducted training/workshops to help people understand the influences that lead to genocide and other great violence, and avenues to prevention, healing and reconciliation. Following this they created educational radio programs for the same ends. The article describes a highly popular radio drama in Rwanda, which has been broadcast since 2004. Evaluation studies of both the effects of the trainings and of the radio drama have found positive effects that are highly relevant for reconciliation. These include more positive attitudes toward the other group, more empathy, more willingness to say what one believes, and more moderate respect for authority (presumably leading to less blind obedience). Anecdotal reports from the community also show the positive effects of the radio drama.